In search of missing links: urbanisation and climate change in Kano Metropolis, Nigeria. Issue 3 (2nd September 2019) - Mohammed, Murtala Uba; Hassan, Nura Ibrahim; Badamasi, Murtala Muhammad
ABSTRACT: The current study examines gaps between climate change and rapid urbanisation sub-Saharan Africa. Through a combined analysis of remotely sensed and meteorological data, the study revealed the extent of urban microclimate change trends within a few decades. Thus, upward changes in microclimate – temperature of nearly 2°C was witnessed in 2018 (27.7°C) against 25.9°C of 1980s. Whereas, the city expanded from 39.2 km 2 in 1986 to 256 km 2 in 2018. These changes witnessed in urban form and climate are attributed to rapid urban expansion and poor planning system that fails to preserve and protect the city's green and blue infrastructure. The picture of the situation in Kano gives insights into the enormous challenges before cities in developing world to cope with local and global climate change risks. Indeed, this situation calls for an integrated approach to addressing climate change from within and without cities themselves. It is imperative on policymakers to increase expenditure on urban planning, financing adaptation strategies through urban planning, and strengthening of institutions of urban planning.